Developmental competence of buffalo (Bubalus bubalis) oocytes: Effect of oocytes quality, protein additives, hormonal supplement and type of capacitating agents - Waheed, M.M.; El-Shahat, K.H.; Hammam, A.M. (Buffalo Bulletin, 2016)
Four experiments were conducted to study the effect of media supplements on in-vitro maturation, cleavage and embryo development of buffalo oocytes. In experiment 1, oocytes were cultured in TCM-199+10% fetal calf serum (FCS) and kept at 39o C under 5% CO2 for in-vitro embryo development. In experiment 2, excellent quality oocytes were subjected to TCM-199 enriched with either 10% FCS or estrous buffalo serum (EBS; 20 to 40 pg/ml) and then fertilized using frozen semen in TALP medium containing heparin (0.02 mg/ml) and caffeine (3.89 mg/ml). In experiment 3, oocytes were cultured in-vitro maturation (IVM) medium supplemented or not with 20 IU/ml equine chorionic gonadotropins (eCG). Experiment 4 was carried out to examine the suitable capacitating agent, either heparin or caffeine or both. Excellent and good quality oocytes produced higher (P<0.05) maturation and morula development rates. In-vitro maturation and cleavage rates were significantly higher (P<0.05) in IVM medium plus EBS or eCG. Heparin and caffeine produced significantly (P<0.05) higher embryo developmental rates. In conclusion, excellent quality oocytes cultured with either EBS or eCG and fertilized with buffalo spermatozoa capacitated with heparin and caffeine progressively enhanced developmental competence of buffalo oocytes.